2004
DOI: 10.1007/s00198-004-1757-4
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status as the major factor determining the circulating levels of parathyroid hormone: a study in normal subjects

Abstract: We investigated the relative contribution of the major factors regulating calcium homeostasis in determining the circulating levels of PTH. We studied 137 males and 125 females who were healthy volunteers. Circulating PTH levels were determined by three different immunoradiometric assays (IRMA). The first one (PTH Sorin, PTH S) utilizes two affinity-purified polyclonal antibodies directed against the 1-34 and 39-84 sequence of the hormone. The two other IRMA share polyclonal anti-PTH (39-84) antibodies. The fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
46
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 38 publications
10
46
0
1
Order By: Relevance
“…A study conducted in postmenopausal women corroborates these findings, reporting no correlation between 25(OH)D and PTH at physiological concentrations (Villareal et al, 1991). Vitamin D only plays a role in the synthesis of PTH, whereas the secretion of the hormone is regulated primarily by calcium (Pepe et al, 2005;Zittermann et al, 1998). We speculate that no change in PTH concentrations was observed in this study as subjects had adequate dietary intakes of calcium, before supplementation with another 1500 mg calcium/day and were not severely deficient in vitamin D.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…A study conducted in postmenopausal women corroborates these findings, reporting no correlation between 25(OH)D and PTH at physiological concentrations (Villareal et al, 1991). Vitamin D only plays a role in the synthesis of PTH, whereas the secretion of the hormone is regulated primarily by calcium (Pepe et al, 2005;Zittermann et al, 1998). We speculate that no change in PTH concentrations was observed in this study as subjects had adequate dietary intakes of calcium, before supplementation with another 1500 mg calcium/day and were not severely deficient in vitamin D.…”
Section: Discussionmentioning
confidence: 80%
“…While Pepe et al (2005) suggested that 25(OH)D concentrations were the main factor determining the circulating levels of PTH, it has also been reported that PTH concentrations only rise when 25(OH)D concentrations are deficient and fall below 40 nmol/l (Mezquita-Raya et al, 2001;Jesudason et al, 2002). In the current study, we did not observe a direct association between 25(OH)D and PTH levels, and observed that even when 25(OH)D concentrations were very low (o30 nmol/l), PTH remained within normal reference ranges.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy adolescents and adults, serum 25OHD concentration has been negatively correlated with serum PTH concentration. 4,6,38,47 This relationship between serum 25OHD and PTH concentrations has not been consistently reproduced in patients with IBD. In accordance with findings in healthy subjects, some investigators found a negative association of serum 25OHD concentration with serum PTH concentration in IBD patients.…”
Section: Discussionmentioning
confidence: 95%
“…Vitamin D deficiency leads to reduced calcium absorption with a tendency towards hypocalcaemia, which stimulates PTH secretion. Thus, decreasing vitamin D leads to increasing levels of PTH (44). Increased PTH for longer periods of time may indeed have harmful effects on the cardiovascular system (7,45,46,47,48,49).…”
Section: Discussionmentioning
confidence: 99%